Unveiling the relationship between self-compassion and emotion regulation among early childhood teachers: A cross-sectional study - Kasman, Apri (Universitas Jambi, Indonesia, 2026)
Early childhood teachers face significant emotional demands in classroom interactions, emphasizing the value of emotion regulation as a critical professional competency. However, many teachers struggle to manage their emotions, which can affect their well-being and teaching effectiveness, leading to increased stress and burnout in their profession. Self-compassion has been recognized as a personal resource that may support adaptive emotional responses. This study aimed to examine the relationship between self-compassion and emotion regulation among early childhood teachers. A cross-sectional survey design was employed, involving 250 teachers selected through purposive sampling. Data were collected using validated self-compassion and emotion regulation scales distributed via an online questionnaire. Pearson correlation analysis revealed a significant positive relationship between self-compassion and emotion regulation (r = 0.62, p < 0.001). The findings indicate that teachers with higher self-compassion tend to demonstrate better emotion regulation. These results suggest the importance of incorporating self-compassion into teacher development programs to enhance emotional competence and professional well-being.